Effect of Mesh Size on Fishing Gear Gill Nets on the Catch in the Sub-District of Teluk Meranti, Pelalawan Regency - Irma Glaudia; Polaris Nasution; Bustari Bustari (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The size of the gill net in the waters of Pangkalan Terap Village is 2.5 inches, 3 inches, and 5 inches, but its use is still based on the current season. This study aims to determine the effect of gillnet mesh size on catches, determine the number, type, weight, and size of catches, and determine the size of gill nets that are effectively used to catch fish in Pangkalan Terap Village. This research was conducted in April - June 2022 in Pangkalan Terap Village, Teluk Meranti District, Pelalawan Regency, Riau Province. The method used in this research is an experimental fishing method with a Randomized Group Design. The results showed that the mesh size of 2.5 inches, 3 inches, and 5 inches in the rainy and dry seasons in Pangkalan Terap Village had a significant effect on the number and weight of fish caught (Fcount> FTable). The number of fish caught in the rainy season was 219 fish weighing 46259 g, while in the dry season, 241 fish weighing 79435g. The types of catches in all nets in both seasons were ten species dominated by Cyclocheillichthys sp. 2.5-inch gill nets are more effectively used because they get the most diverse catches compared to other nets